The Erosion of the Rule of Law in Eritrea: Silencing Freedom of ExpressionPromoting Citizenship and Preventing Statelessness in South Africa: A Practitioner's Guide - Authors: Centre for Human Rights, University of Pretoria and UN Mandated University for Peace, St Jose, Costa Rica (Pretoria University Law Press (PULP), 2015)
About the publication This report contains an in depth analysis of the muted right to freedom of expression in Eritrea. The number and forms of human rights violations related to the curtailing of free speech have been and continue to be well documented across the globe. This discourse identifies the right to free reception of information and expression as the bedrock to realising and maintaining the rule of law. Investigated herein is the historical background to the political evolution of the small African state and the social impact of the prevailing human rights violations. This report contains a compilation of human rights violations as determined by international treaty bodies, interviews with Eritrean witnesses and diaspora in exile and civil society reports on the human rights situation. It is argued in the report that the absence of the rule of law in Eritrea is directly attributed to the collapse of free expression as political forces see this right as a threat to their power base - a form of suppression that has nullified all human rights and freedoms and might well damage its people beyond repair. Table of Contents Preface List of abbreviations List of Eritrean print and electronic media Acknowledgments Executive summary English Executive summary French Executive summary Tigrinya Executive summary Arabic Introduction Contextualising the rule of law in Eritrea Eritrea's human rights obligations and rule of law Non-Implementation of the Eritrean Constitution Suppression of free expression as an attack on the rule of law in Eritrea Prelude to dictatorship: Human rights before September 2001 The Crackdown of September 2001 Free expression in Eritrea today: Effects of widespread reprisals Closure of non-state media houses Collapse of the journalistic profession in Eritrea Internet censorship From arbitrary arrests to subtle control of the message Pervasive editorial spin The '03' rumour system Suppression of foreign and diaspora media Reporting the work of the courts Eritrea's international relations Awareness of the dangers of refugee flight Rebirth of independent journalism Recommendations Annex I: Compilation of recorded human rights violations related to free speech Arbitrary arrest and detention Torture and other cruel, inhuman or degrading treatment or punishment Death in custody Annex II: Report of the Working Group on the Universal Periodic Review: Eritrea I. Recommendations accepted II. Recommendations that do not enjoy the support of Eritrea